Середньовічні городища Дніпровського Лівобережжя із залишками водозбірних споруд - Жигола, В.С. (Археологія, 2011)
Розглядається ситуація довкола сіверянських та давньоруських городищ Дніпровського Лівобережжя із залишками водозбірних споруд. Особенной чертой некоторых городищ на территории Украины, в частности Левобережья Днепра конца І — начала ІІ тыс., является наличие всередине защищенной площадки больших ям, которые исследователи определяют как водосборные резервуары или колодцы. В историографии им уделено немного внимания, так как они плохо исследованы. По нашему мнению, для полного раскрытия вопроса нужно указать возможное более точное датирование ямколодцев. Поставленная задача требует создания каталога левобережных городищ с ямамиколодцами с учетом их параметров. В него внесены 16 объектов, описанных М.П. Кучерой, а также добавлено не упомянутое им городище, исследованное Ю.Ю. Моргуновым. На основе составленного каталога можно сделать выводы об общих чертах описанных памятников, что позволит в целом лучше разобраться в поднятом вопросе. Площадь всех городищ или их детинцев с ямамиколодцами всегда менее 1,0 га. Городища размещаются на высоких мысах или останцах. Другой общей чертой есть геометрически округлая или приближенная к такой форма оборонительных сооружений или площадок городищ. В 11 по периметру есть оборонительные сооружения — вокруг площадки или ямыколодца. Главной общей чертой всех перечисленных городищ есть наличие возле них открытых поселений, посадов или других городищ: 14 из них имеют рядом селища площадью от 1,5 до 25 га. Единственной ямойколодцем достоверно роменского времени может считаться объект на однослойном городище Заречное, которое принадлежит лишь роменской культуре. Также на шести ородищах отмечено роменский культурный слой, перекрытый древнерусским, но устройство объектов можно датировать северянским временем. Ямыколодцы на четырех памятниках, вероятнее, возведены не северянским населением и хронологически принадлежат к древнерусскому времени. Остальные шесть памятников имеют культурные отложения в рамках Х — средины ХІІІ вв. На некоторых из них оборонительные сооружения возникли уже в древнерусское время. Ямыколодцы этой группы без детальных раскопок датировать невозможно. То есть, все сооружения возводились и населением роменской культуры, и во времена Киевской Руси. Описанные поселения играли важную роль как в северянском обществе (центры протоагломераций, некоторых групп населения), так и в Древнерусском государстве (уже являются протогородами, размещаются на защищенном пограничье). Следует заметить, что дальнейшая разработка темы нуждается в детальном исследовании всех объектов, их конструкций, функции и датирования. The peculiar feature of certain hillforts on the territory of Ukraine, particularly on the left bank of the Dnipro River of the 1st and the beginning of the 2nd millennia, is the existence in the centre of the protected areas of large pits which are determined by the scholars as drain reservoirs or wells. They are given little consideration in historiography because they are hardly studied. In the author’s opinion, for the full resolution of this issue it is necessary to determine possible more precise dating of the pitswells. The assigned task requires creating a catalogue of the left bank hillforts with the pitswells taking into account their parameters. Into the catalogue there have been included 16 objects described by M.P. Kuchera, as well as a hillfort not mentioned by him but studied by Yu.Yu. Morhunov. Based on the catalogue it is possible to make conclusions about the general features of the sites described which will allow to understand better the raised issue in general. Area of all hillforts or their dytynets (citadel) with pitswells is always less then 1,0 hectare. Hillforts are situated on high headlands or outliers. Another common feature is geometrically rounded or close to that the form of defensive structures or areas of the hillforts. 11 hillforts have in their perimeter defensive structures: around the area or around the pitwell. The main common feature of the hillforts mentioned is the existence of undefended settlements, posads (trading quarters) or other hillforts: 14 of them have settlements of the area from 1,5 to 25 hectares next to them. The only pitwell authentically of the Romenska culture period can be considered an object at Zarichne hillfort which is singlelayered and belongs only to Romenska culture. Also, the layer of Romenska culture was identified at six hillforts and it was covered with the Ancient Rus period layer but the arrangement of objects can be dated by the Siveryans period. Pitswells at four sites most probably were constructed not by the Siveryans, and they chronologically belong to the Ancient Rus period. The other six sites contain cultural deposits within the period from the 10th c. to the middle of the 13th c. Defensive structures at some of them appeared in the Ancient Rus period already. Pitswells of this group can not be dated without the detailed excavations. In other words, all structures were erected both by the population of Romenska culture, and during the times of Kyiv Rus. The settlements described played an important role both in the community of the Siveryans (centres of protoagglomeration and of certain groups of population), and in the Ancient Rus state (they already become protocities, and are situated in the protected frontier). It should be noted that the further development of the issue requires the detailed research of all objects, of their constructions, function and dating. The only pitwell authentically of the Romenska culture period can be considered an object at Zarichne hillfort which is singlelayered and belongs only to Romenska culture. Also, the layer of Romenska culture was identified at six hillforts and it was covered with the Ancient Rus period layer but the arrangement of objects can be dated by the Siveryans period. Pitswells at four sites most probably were constructed not by the Siveryans, and they chronologically belong to the Ancient Rus period. The other six sites contain cultural deposits within the period from the 10th c. to the middle of the 13th c. Defensive structures at some of them appeared in the Ancient Rus period already. Pitswells of this group can not be dated without the detailed excavations. In other words, all structures were erected both by the population of Romenska culture, and during the times of Kyiv Rus. The settlements described played an important role both in the community of the Siveryans (centres of protoagglomeration and of certain groups of population), and in the Ancient Rus state (they have already become protocities, and were situated in the protected frontier). It should be noted that the further development of the issue requires the detailed research of all objects, of their constructions, function and dating.